Methodical Approach to Design of System of the Logistic Centers and Wholesale Warehouses at the Regional Level - BAKHTIZIN, Ramil; EVTUSHENKO, Evgenii; BURENINA, Irina; GAISINA, Lyutsiya; SAGITOV, Salavat (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
The object of this research is the regional logistic infrastructure. The subject of research is development of the logistic infrastructure of the region due to the system implementation of the logistic centers and wholesale warehouses. The strategic aim – is development of a universal methodology for designing the system of the logistic centers and wholesale warehouses with taking cue from the features of the concrete region of the Russian Federation. The principles of systematic approach, coordination and integration, scientifically and consistence, global optimization, minimization of logistic expenses, simulation, information and computer support, the principle of synthesis are the basis for development of split-level of approaches and a method of zone planning. In order to choose the location of the logistic center the method of ‘center of gravity’ has been used. The methodology includes a set of stages of preparation and the analysis of information for zone planning with taking into consideration expected changes of material flows, direct zone division of the territory with justification of the proposed solutions with the subsequent specification in the form of program of actions and complex social and economic assessment of location of logistic capacities. The main stages of realization of a methodology include: the analysis of requirement of transport companies of the region, commodity producers, the enterprises of wholesale and retail trade in the logistic centers and wholesale warehouses; determination of market capacity of logistic services of the region, in particular on the basis of ‘production consumption’ matrix (interindustry balance) of a region of the Russian Federation and adjacent regions; definition of need for warehouses of temporary storage; zone planning of the region, definition of the zone centers taking into consideration the flows– transport, goods and services, labor and money; working out a plan of measures on development of system of the logistic centers and wholesale warehouses in the territory of the region in mid-term prospect; assessment of social and economic efficiency of implementation of the program. The realization of the program of development of the logistic centers system and wholesale warehouses in the Republic of Bashkortostan became testing of the offered methodology. Extending of experience in using of this methodology for other regions of the Russian Federation will allow to accelerate development of logistic infrastructure of regions and, respectively, in general of the Russian Federation.